Incidence and prevalence of lumbar stress fracture in English County Cricket fast bowlers, association with bowling workload and seasonal variation. Issue 1 (12th May 2019) - Alway, Peter; Brooke-Wavell, Katherine; Langley, Ben; King, Mark; Peirce, Nicholas
Abstract : Objectives: Since much of the previous epidemiological research into lumbar stress fracture was conducted, there has been a marked increase in the amount of cricket being played. The aims were to determine the incidence and prevalence of lumbar stress fracture in English County Cricket fast bowlers between 2010 and 2016, determine the association with match bowling workload and observe seasonal variation in workload and injury. Methods: Lumbar stress fracture incidence and prevalence rates were calculated using new international methods for epidemiology in 368 professional English fast bowlers from 2010 to 2016. Workload variables were compared between lumbar stress fracture case and non-injured control groups, before entry in a logistic regression. Results: Fifty-seven lumbar stress fractures (mean age 22.81) were reported. Injury was most common in July and September. Match incidence was 0.16 lumbar stress fractures per 10 000 deliveries, annual incidence was 2.46 lumbar stress fractures per 100 fast bowlers and annual prevalence of lumbar stress fractures was 1.67% of squad days. Significant workload variables were observed between cases and controls. A peak 7-day workload of greater than 234 deliveries significantly increased the odds of sustaining a lumbar stress fracture 11-fold compared with bowling fewer than 197 deliveries. Conclusion: Lumbar stress fractures are common in young fast bowlers possibly due to immaturity of the lumbar spine. The condensed early and late-season schedule may be causing periods of overuse, resulting in an increase in incidence of lumbar stress fracture. Reduction of workload in young fast bowlers is needed to reduce incidence.